2007
DOI: 10.1016/j.jasms.2006.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cationic free-base meso-tris-N-methylpyridinium-4-yl porphyrins in positive mode electrospray ionization mass spectrometry

Abstract: Reductions involving more than one electron with formation of the M ϩ and [Mϩ2H] ϩ ions were observed for electrosprayed meso-tris (N-methylpyridinium-4-yl)porphyrin iodides, MI 3 . These reductions were studied by using different solvents and flow rates. Formation of the [Mϩ2H] ϩ ions occurred only for protic solvents and to a larger extent at lower flow rates. The type of the fourth substituent does not seem to affect the reduction processes. , it is generally accepted that redox reactions do occur in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
5
10
1
Order By: Relevance
“…Contrary to aliphatic ammonium hypervalent radicals that are transient species,19 aromatic hypervalent radicals are stabilized by partial charge delocalization throughout the macrocycle and are relatively stable. Although similar one‐electron reductions have been reported for aromatic quaternary ammonium salts, since 1980,12 by using several ionization techniques,14, 16, 19, 22, 23 multielectron reductions are less common 11. In the present case, the formation of the reduced species is not dependent on the structure of the counter ions, as reduction occurs for TMPyP with both the I − and p ‐CH 3 C 6 H 4 SO 3 − counter ions.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Contrary to aliphatic ammonium hypervalent radicals that are transient species,19 aromatic hypervalent radicals are stabilized by partial charge delocalization throughout the macrocycle and are relatively stable. Although similar one‐electron reductions have been reported for aromatic quaternary ammonium salts, since 1980,12 by using several ionization techniques,14, 16, 19, 22, 23 multielectron reductions are less common 11. In the present case, the formation of the reduced species is not dependent on the structure of the counter ions, as reduction occurs for TMPyP with both the I − and p ‐CH 3 C 6 H 4 SO 3 − counter ions.…”
Section: Resultssupporting
confidence: 73%
“…Reduction of multiply‐charged free base porphyrins, with formation of M + and [M + 2H] + ions, when using ESI‐MS in the positive ion mode, was first observed by us for the iodide salts of meso ‐tris( N ‐methylpyridinium‐4‐yl)porphyrins, MI 3 11. We suggested that these new species could be hypervalent radicals formed by multielectron reduction or protonation plus multielectron reduction of the M 3+ porphyrin cations, through the participation of counter ion/solvent adducts 11…”
Section: Introductionmentioning
confidence: 99%
“…As expected and similar to ( N ‐alkylpyridinium‐4‐yl)porphyrins, for compounds 1 to 5 , the most abundant product ions of the M 3+ precursors are formed by loss of one methyl radical, [M − 15] 3+ , which confirms their predominant hypervalent mono‐radical character. Other less abundant product ions are present, namely, the [M − 31] 3+ , [M − 42] 3+ , [M − 56] 3+ , and [M − 96] 3+ ions.…”
Section: Resultssupporting
confidence: 78%
“…In contrast, the formation of the [M − 145] 2+ ion may be ascribed to a loss of the DCP substituent by scission of the C–C meso ‐bond, which is similar to the losses observed for other porphyrins containing meso ‐substituents with six‐membered rings . Thus, the [M − 227] 2+ = [M − 145 − 27 − 55] 2+ ion may be formed by loss of the DCP substituent and by losses of 27 and 55 Da, from the protonated and from one of the neutral substituents, respectively.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation